Perpetuation of Alternaria sesami causing blight of sesame in seeds and plant debris - P.S. PRASAD; K. RAJU, M.K. NAIK*, A.S. SAVITHA, R. LOKESHA, (Indian Phytopathology, 2007)
Seeds of sesame obtained from Alternaria infected plants were subjected to agar tests after a week of harvest at weekly intervals for finding out the extent of seed transmission of Alternaria sesami. The seed transmission of the fungus was observed up to 59 weeks after harvest. However, the extent of seed transmission varied with increasing period after harvest. The extent of seed transmission was 34.13 per cent in the first week after the harvest while 33.46 per cent in the second week. However, the extent of seed transmission was just only 0.80 per cent during 58th week of harvest and no Alternaria sesami was detected from the seed lots beyond 59 weeks. The result is of great concern that this pathogen, A. sesami can survive in seed up to 11 months and seed treatment is essential to check the pathogen. The survival of the pathogen was found up to 18 months in the infected debris kept in laboratory, 21 months in refrigerated conditions, but under field condition the fungus was recovered up to 11 months. The result implies that the pathogen can perpetuate in infected debris for nearly 11 months under field condition and can serve as source of inoculum.